(untitled) (قضايا سياسية, 2025)
This research aims to evaluate the success of Abdolkarim Soroush's Theory of Expansion and Contraction in addressing the intellectual and political challenges that have accompanied the development of Iranian society. This is particularly relevant to the realm of religious reform, which extends beyond theological boundaries to encompass diverse political objectives. The study identifies the obstacles encountered in the Iranian context. The nature of the subject and the research mechanisms necessitated the use of both descriptive-analytical and critical methodologies, as they fulfill the researcher's epistemological needs and are congruent with the approach to hypothesis testing and the scientific means for providing precise answers to the research problem's question. After adopting a methodological framework for the research, comprising four chapters as key research junctures discussed using tools of description, analysis, and critique, the research reached several prominent conclusions. These include the success of Soroush's theory in presenting a renewed vision for religious thought, imbuing it with flexibility by linking it to various epistemological contexts to keep pace with cognitive advancements in all scientific fields, and its pursuit of comprehensive political reforms. Furthermore, the study attributes the theory's failure to social, political, intellectual, and methodological obstacles encountered during its application in Iran. These limitations curtailed its impact and success, confining the theory to a limited practical effect and largely theoretical framework, despite representing a significant intellectual and scientific endeavor attributed to its proponent, Abdolkarim Soroush.